Dissociative Symptoms Among Individuals Affected by Mass Psychogenic Illness: A Study on the Indonesian Island of Nias - Michael Seno Rahardanto; Jaka Santosa Sudagijono; Johannes Dicky Susilo; Simon Simon; Nurul Hartini; Rahkman Ardi (Journal of Educational, Health and Community Psychology, 2024)
Mass psychogenic illness is a phenomenon that occurs every year in Indonesia, mainly in schools and factories. In the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders, this phenomenon is classified as dissociative disorders. However, the Indonesian diagnostic manual of mental disorders (the PPDGJ) classified the phenomenon as a conversion disorder. The confounding diagnosis will likely result in less effective and less humane interventions. This study aims to determine the symptoms experienced by individuals experiencing mass psychogenic illness, therefore contributing to the current literature regarding the proper diagnostic of the spirit possession. Samples (N=55) were assessed using the Dissociative Disorder Interview Schedule based on DSM-5. The Beck Depression Inventory and Wong-Baker Face Rating Scale are also used to supplement the data. Findings indicate that the subjects fit the diagnostic criterion of several disorders, namely somatization (experienced by 98.18% of individuals), major depression (49%), trance (69%), childhood physical abuse (35%), and borderline personality disorder (47.2%). However, only 14.54% of subjects fulfilled the diagnostic criterion of dissociative amnesia, 7.27% for diagnostic fugue, 3.63% for depersonalization/derealization, 5% for dissociative identity disorder, 11% for other specified and unspecified dissociative disorder. These findings showed that mass psychogenic illness is likely the manifestation of distinct and separate mental disorders, notably that of somatization disorder, trance, borderline personality disorder, and major depressive disorder, and exclusively those of dissociative disorders.